2014
DOI: 10.1016/j.ajog.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma, bacterial vaginosis–associated bacteria BVAB3, race, and risk of preterm birth in a high-risk cohort

Abstract: OBJECTIVE Genital tract infection accounts for ~ 25–40% of all pre-term births. We sought to assess the relationship between preterm birth and selected vaginal bacterial taxa associated with preterm birth either directly or through their association with bacterial vaginosis (BV). STUDY DESIGN Vaginal fluid for Gram stain was collected between 17 and 22 weeks gestation as part of a randomized trial of ultrasound-indicated cerclage for preterm birth prevention in women at high risk for recurrent spontaneous pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 20 publications
(29 reference statements)
4
59
0
4
Order By: Relevance
“…Furthermore, using antibiotic prescriptions as a surrogate for health care utilization, antibiotics were more frequently prescribed in the non–large urban cohorts for nongenitourinary infections. Confirming negative effects seen by others (5,28,29,31), our study did not show a reduced risk for preterm birth with the non-randomized prescription of antibiotics considered active against urogenital mollicutes, possibly due to reinfection, antibacterial resistance, inadequate drug levels at site of infection, or lack of eradication secondary to non-bacteriocidal therapy (5,31,32,33,34). …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, using antibiotic prescriptions as a surrogate for health care utilization, antibiotics were more frequently prescribed in the non–large urban cohorts for nongenitourinary infections. Confirming negative effects seen by others (5,28,29,31), our study did not show a reduced risk for preterm birth with the non-randomized prescription of antibiotics considered active against urogenital mollicutes, possibly due to reinfection, antibacterial resistance, inadequate drug levels at site of infection, or lack of eradication secondary to non-bacteriocidal therapy (5,31,32,33,34). …”
Section: Discussionsupporting
confidence: 87%
“…In contrast, a recent Brussels study (28) of nearly 2000 pregnancies found Ureaplasma species to be a significant risk for preterm birth, and a commensurate risk of preterm birth was associated with abnormal flora, but only if Ureaplasma species was culture positive. These variable results may be related to differences in vaginal ecologies as recently described in studies of high-risk pregnancies (29,30). …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We tested for associations between PTB and increased gestational frequencies of several genera frequently linked with BV (Gardnerella, Prevotella, Atopobium, Mobiluncus, Megasphaera, Dialister, Peptoniphilus, and Mycoplasma) and three sequence variants that exactly matched 16S rRNA genes from the recently identified bacterial vaginosisassociated bacteria BVAB1, BVAB2, and BVAB3 (23,24). Prevotella was associated with PTB in both cohorts (P < 0.05), while most of the remaining genera were significantly associated only in the Stanford cohort (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Foxman et al . evaluated the role of several BV-associated bacteria with preterm birth and reported that pregnant women having this organism had a decreased risk of preterm delivery [39]. BV has been linked with increased shedding of HIV [1].…”
Section: Resultsmentioning
confidence: 99%